Nonerythroid Hemoglobin Present in Porcine Testes - Jeffrey Li; Barbara Jean Nitta; Trish Berger (Animals)
The presence of hemoglobin beta mRNA and protein in the female gonad suggests that hemoglobin beta may be present in the male gonad as well. The frequent occurrence of hemoglobin beta in nonerythroid tissues with hypoxic environments further underscores a potential role for hemoglobin beta in the testis to facilitate the regulation of oxygen availability for the developing germ cells and Sertoli cells since they are separated from the blood supply by multiple tissues. The presence of mRNA and protein were evaluated by qPCR and immunohistochemistry, respectively. The mRNA and protein for hemoglobin were detected in juvenile and postpuberal porcine testes. The most intense immunolabelling for the protein was present in testicular interstitial cells, in contrast to previously reported ovarian labelling in close proximity to the gamete and observed in porcine ovaries in the current study. The observed decrease in mRNA expression of hemoglobin beta with age is probably due to the change in testicular composition (increase in seminiferous tubule compartment) with age. The localization of hemoglobin beta in the testis will contribute to future understanding of its potential function in facilitating oxygen availability to seminiferous tubules or reducing oxidative damage.